The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1996
DOI: 10.3354/meps134309
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying the short-term temperature effect on light-saturated photosynthesis of intertidal microphytobenthos

Abstract: A mathematical expression is proposed to describe the relationship between the photosynthetic capacity (P,,,,) of natural assemblages of motile benthic diatoms and temperature. Experiments were performed in 2 different seasons to document the response of P,,,, to a rapid increase in temperature (3°C h-'). In both cases, there was a progressive increase in P,,,,, up to an optimum temperature (Top,). beyond which P,,,,, declined rapidly. Top, did not change from September to December 1995, but the maximum photos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
95
3

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 121 publications
(102 citation statements)
references
References 9 publications
4
95
3
Order By: Relevance
“…The significant variations of abundance and chl a concentration found in May 2008 and May 2009 are probably related to the difference in sediment surface temperature (difference between the two months: 11 C). In general, seasonal changes in intertidal systems subjected to large fluctuations of various environmental factors can mostly be explained by specific adaptations to light and temperature conditions (Cade´e & Hegeman, 1974;Grant, 1986;Blanchard et al, 1996;Barranguet et al, 1998). In the present investigation, the seasonal dynamics of the different MPB groups showed very similar patterns at the different stations (cf.…”
Section: à2supporting
confidence: 56%
“…The significant variations of abundance and chl a concentration found in May 2008 and May 2009 are probably related to the difference in sediment surface temperature (difference between the two months: 11 C). In general, seasonal changes in intertidal systems subjected to large fluctuations of various environmental factors can mostly be explained by specific adaptations to light and temperature conditions (Cade´e & Hegeman, 1974;Grant, 1986;Blanchard et al, 1996;Barranguet et al, 1998). In the present investigation, the seasonal dynamics of the different MPB groups showed very similar patterns at the different stations (cf.…”
Section: à2supporting
confidence: 56%
“…In contrast, high irradiance levels did not correspond to an enhanced de-epoxidation state at the Eden estuary, where the de-epoxidation state was higher in winter than in summer. Temperature was possibly a factor that affected xanthophyll pigment cycling because temperatures decrease the rates of enzyme reactions (Grant, 1986;Blanchard et al, 1996). With metabolic processes slowing down, the energy demand of the cells will decrease.…”
Section: Discussionmentioning
confidence: 99%
“…This generally accepted scheme categorises the gross photosynthetic response for both Nivå Bay and the Trondheimsfjord as psychrotrophic. Studies from the Danish and Dutch Wadden Seas, applying other techniques, have shown lower-end mesophile temperature responses of gross photosynthesis, with T opt of 15 to 30°C (Colijn & van Buurt 1975, Rasmussen et al 1983, Blanchard et al 1996.…”
Section: Phototrophic Temperature Responsementioning
confidence: 99%
“…In shallow waters, both variables change on a seasonal and a diel basis superimposed by tidal and weather-driven variations, all having an impact on the benthic microbial activity (Grant 1986, Cahoon 1999, Glud et al 2002. Studies at subtidal and intertidal sites have shown that temperature can exert tight control on benthic photosynthetic rates, and can lead to seasonal acclimation and/or change in the microphytobenthic community composition (Rasmussen et al 1983, Grant 1986, Blanchard et al 1996, Barranguet et al 1998. Temperature acclimation usually describes phenotypic changes in a community as a response to short-term temperature change, whereas temperature adaptation involves genetic differences in metabolism between communities from different thermal environments (Berry & Bjorkman 1980, Davison 1991.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation